The Interplay Between Prolactin and Reproductive System: Focus on Uterine Pathophysiology - Auriemma, Renata S.; Del Vecchio, Guendalina; Scairati, Roberta; Pirchio, Rosa; Liccardi, Alessia; Verde, Nunzia; de Angelis, Cristina; Menafra, Davide; Pivonello, Claudia; Conforti, Alessandro; Alviggi, Carlo; Pivonello, Rosario; et al. (Frontiers in Endocrinology, 2020)
Over the last years, increasing evidence has focused on crucial pathogenetic role of PRL on malignant, premalignant and benign uterine diseases. Studies in animals and humans have documented that PRL receptors (PRL-Rs) are widely expressed on uterine cells and that PRL is directly synthesized by the endometrium under the stimulatory action of progesterone. Uterine PRL secretion is finely modulated by autocrine/paracrine mechanisms which do not depend on the same control factors implied in the regulation of PRL secretion from pituitary. On the other hand, PRL is synthesized also in the myometrium and directly promotes uterine smooth muscle cell growth and proliferation. Therefore, PRL and PRL-Rs appear to play an important role for the activation of signaling pathways involved in uterine cancers and preneoplastic lesions. Circulating PRL levels are reportedly increased in patients with cervical or endometrial cancers, as well as uterine premalignant lesions, and might be used as discriminative biomarker in patients with uterine cancers. Similarly, increased PRL levels have been implicated in the endometriosis-induced infertility, albeit a clear a causative role for PRL in the pathogenesis of endometriosis is yet to be demonstrated. This evidence has suggested the potential application of dopamine agonists in the therapeutic algorithm of women with malignant, premalignant and benign uterine lesions. This review focuses on the role of PRL as tumorigenic factor for uterus and the outcome of medical treatment with dopamine agonists in patients with malignant and benign uterine disease.